Book Clubs and Book Commerce - Norrick-Rühl, Corinna (Humanities, 2019)
In the twentieth century, cumulative millions of readers received books by mail from clubs like Book-of-the-Month Club. This Element offers an introduction to book clubs as a distribution channel and cultural phenomenon, and shows that book clubs and book commerce are linked inextricably. This title is also available as Open Access on Cambridge Core.